Electronic information resources: definition and classification - Myliutchenko, I.O.; Kulko, P.O. (Radiotekhnika, 2023)
The article provides a review of normative documents and scientific works devoted to the concept of "electronic information resource" as an important type of information resources, caused by the influence of information technologies. The classification of electronic information resources is given, summarizing the most common features and categories and also taking into account the correspondence between the features of the classification of information resources and electronic information resources.